(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2018)
Over the past few decades debates in the field of conservation have called into question the suppositions underpinning contemporary restoration theory and practice. Restorers seem to base their choices on implicit ideas about the authenticity, identity and value of works of art, ideas that need to undergo a more systematic theoretical evaluation. I begin by focusing on the question of whether authenticity is fully established in the process of the creation of an artwork: namely, at its initial point of existence. One’s interpretation of what makes an artwork authentic will indeed greatly influence how to go about preserving or restoring it. If the answer to the question is affirmative (1), one commits to the idea that authenticity is determined by the work’s creator; thus, it is considered a given, exempt from historical flux. If the answer is negative (2), one takes authenticity to be a combination of initial creation and temporal change; in this sense the work is considered a ‘historical being’. These two conceptions, in turn, come from opposite ontological perspectives on the identity of artworks. Neither of them, however, proves to be truly convincing. I argue that from the point of view of conservation theory we need to consider artworks neither like physical objects nor like living beings, but rather like social objects in Searle’s sense. To this extent, safeguarding authenticity in conservation goes hand in hand with preserving a work’s continuity through enhancing what I call its structural and aesthetic readability. Restoration is thus in its essence a critical act of interpretation which has more to do with the various meanings of an artwork than with its hypothetical original conditions. Rather than just being a win-or-lose affair, authenticity turns out to be the result of a complex set of mutually interacting variables.